(untitled) (European Journal of Health Research, 2024)
The burnout is a topic in the field of occupational health that has been worked during the last deans, which is a chronic wear, produced by stress, it is considered important to work in professionals of the educational field in virtue of the topic of pandemic and perception of some teachers has interpreted this transmission as an adverse load and stressful the topic of telework. The objective of the present investigation was to identify the existing relation between burnout and mental health in a sample of teachers. A cross-sectional methodology with a quantitative approach was used, with a correlational design, with a non-probabilistic sample of 178 teaching professionals, using Maslach and Jackson’s MBI Inventory and the Depression, Anxiety and Stress Scale DASS-21. The results reveal that most of the teachers had an average of emotional exhaustion 15.69 and depersonalization 3.6, a mean of personal accomplishment 39.24. With respect to mental health, the highest mean was stress with 4.16, followed by anxiety 3.05 with a mean of and depression of 2.65. Among the most important correlations, it was possible to identify the relationship between anxiety, depression and stress with emotional fatigue, depression and depersonalization and personal fulfillment with each of the scales: anxiety, depression and stress. It is considered important to work in clinical practice based on these results to implement lines of action to reduce stress within educational organizations.